Exploring the Use of Helicogenic Amino Acids for Optimising Single Chain Relaxin-3 Peptide Agonists - Han Siean Lee (Biomedicines, 2020)
Relaxin-3 is a highly conserved two-chain neuropeptide that acts through its endogenous receptor the Relaxin Family Peptide-3 (RXFP3) receptor. The ligand/receptor system is known to modulate several physiological processes, with changes in food intake and anxiety-levels the most well studied in rodent models. Agonist and antagonist analogues based on the native two-chain peptide are costly to synthesise and not ideal drug leads. Since RXFP3 interacting residues are found in the relaxin B-chain only, this has been the focus of analogue development. The B-chain is unstructured without the A-chain support, but in single-chain variants structure can be induced by dicarba-based helical stapling strategies. Here we investigated whether alternative helical inducing strategies also can enhance structure and activity at RXFP3. Combinations of the helix inducing α-aminoisobutyric acid (Aib) were incorporated into the sequence of the relaxin-3 B-chain. Aib residues at positions 13, 17 and 18 partially reintroduce helicity and activity of the relaxin-3 B-chain, but other positions are generally not suited for modifications. We identify Thr21 as a putative new receptor contact residue important for RXFP3 binding. Cysteine residues were also incorporated into the sequence and cross-linked with dichloroacetone or α, α’-dibromo-m-xylene. However, in contrast to previously reported dicarba variants, neither were found to promote structure and RXFP3 activity.